Review Of Returning Medical Records In Outpatient Medical Record - Minda Kusumah, Raden; Putri Meyliyan, Jessica (Jurnal KESANS : Kesehatan dan Sains, 2021)
In returning the outpatient medical record file to thesection of the Medical Record Unit, Assembling there was a delay. This is because the return of medical record files has not been carried out according to Standard Operating Procedures, as a result, causing delays in the reporting system. The method used is qualitative using a descriptive approach. Data collection techniques by observation, interviews and literature study. This study aims to determine the return of former medical records of outpatients at Dayeuhkolot Health Center. The results of the study prove that the delay in returning outpatient medical record files at the Dayeuhkolot Health Center with presentations during the 1 week study amounted to 63 or 22% of 285 medical record files. Efforts have been made to disseminate information to all officers related to the efforts made by the person in charge of COVID-19 patients in returning medical record files on time.